Odorant receptor-based discovery of natural repellents of human lice. (November 2015) - Pelletier, Julien; Xu, Pingxi; Yoon, Kyong S.; Clark, John M.; Leal, Walter S.
Abstract: The body louse, Pediculus humanus humanus, is an obligate blood-feeding ectoparasite and an important insect vector that mediates the transmission of diseases to humans. The analysis of the body louse genome revealed a drastic reduction of the chemosensory gene repertoires when compared to other insects, suggesting specific olfactory adaptations to host specialization and permanent parasitic lifestyle. Here, we present for the first time functional evidence for the role of odorant receptors (ORs) in this insect, with the objective to gain insight into the chemical ecology of this vector. We identified seven putative full-length ORs, in addition to the odorant receptor co-receptor (Orco), and expressed four of them in the Xenopus laevis oocytes system. When screened with a panel of ecologically-relevant odorants, PhumOR2 responded to a narrow set of compounds. At the behavior level, both head and body lice were repelled by the physiologically-active chemicals. This study presents the first evidence of the OR pathway being functional in lice and identifies PhumOR2 as a sensitive receptor of natural repellents that could be used to develop novel efficient molecules to control these insects. Graphical abstract: Highlights: Odorant receptors of the body louse were screened by a panel of ecologically-relevant chemicals. An odorant receptor, PhumOR2, responded to a narrow subset of odorants with high sensitivity. Three physiologically-active compounds elicited strong avoidance behavior in both head and body lice. PhumOR2 functions as a biological detector of natural repellents in lice. These findings advance our understanding of lice chemical communication and promote novel control strategies against lice.